Effect of Rehabilitation Program on Endocrinological Parameters in Patients with COPD and in Healthy Subjects. (1st December 2014) - Mkacher, Wajdi; Tabka, Zouhair; Chaieb, Faten; Gueddes, Meriem; Zaouali, Monia; Aouichaoui, Chirine; Zbidi, Abdelkrim; Trabelsi, Yassine
Abstract Background: Skeletal muscle wasting commonly occurs in patients with chronic obstructive pulmonary disease (COPD) and has been associated with the presence of systemic inflammation and endocrinological disturbance. The aim of this study is to analyze the effect of rehabilitation program on the balance of anabolic versus catabolic hormone in patients with COPD and in healthy subjects. Methods: Nineteen patients with COPD and 16 age-matched healthy subjects undertooked exercise training 3 days/week for 8 weeks. Before and after the training program the concentration of growth hormone (GH), Insulin-Like Growth Factor-1 (IGF-1), Insulin-like Growth Factor-Binding Protein 3 (IGF-BP3), testosterone and cortisol in serum were determined. The exercise measurements included a 6-Minute Walking Test (6MWT). Results: After 8 weeks, there was no significant change in lung function in patients with COPD and healthy subjects. Growth hormone, Insulin-like Growth Factor-1 and Insulin-like Growth Factor-Binding Protein 3 increased significantly after rehabilitation training (p < 0.01). The rehabilitation program improves the testosterone/cortisol ratio (T/C ratio) in both groups. There is a significant improvement in the 6-Minute Walking distance (6MWD) in both groups (p < 0.01). Dyspnea and heart rate at rest and at the peak of the 6-Minute Walking Test (6MWT) decreased significantly after training program (p < 0.01). Conclusion: Pulmonary rehabilitation induces an improvement of the anabolic process and reduces proteine distruction by the modifications in endocrinological factors regulating skeletal muscle in patients with COPD.